Profile of Scientific Literacy Skills on The Subject of Global Warming Senior High School in Jember - Dini Atrasina Ludyas Adani; Sutarto Sutarto; Slamet Hariyadi (Eduvest - Journal of Universal Studies, 2022)
In the 21st century, students are required to have scientific skills that are used to face globalization with advances in technology and knowledge. One of the skills that must be possessed by students is scientific literacy skills. Scientific literacy is very important to be owned and understood by students because students can analyze and understand the relationship between scientific concepts and problems that exist in the environment around students. This study analyzes profil of scientific literacy in class XI students in several high schools in Jember Regency. Scientific literacy indicators include explaining scientific phenomena, analyzing and interpreting data to draw conclusions, as well as evaluating and designing. This type of research is descriptive research with data collection by google form. Based on the google form, shows that 58% of indicators explain scientific phenomena with low category, for indicators to analyze and interpret data to draw conclusions to get 48% data in the very low category, while evaluating and designing indicators get 59% in the low category. Based on these data, it shows that the scientific literacy skills of class XI students in Jember City is still low.